Invasive Breast Carcinoma with Neuroendocrine Differentiation: A Single-Center Analysis of Clinical Features and Prognosis - Krawczyk, Natalia; Röwer, Rowena; Anlauf, Martin; Muntanjohl, Caja; Baldus, Stephan Ernst; Neumann, Monika; Banys-Paluchowski, Maggie; Otten, Sabine; Luczak, Katharina; Ruckhäberle, Eugen; Mohrmann, Svjetlana; Hoffmann, Jürgen; Kaleta, Thomas; Jaeger, Bernadette; Esposito, Irene; Fehm, Tanja (Geburtshilfe und Frauenheilkunde, 2021)
Introduction Invasive breast cancer with neuroendocrine differentiation is a rare subtype of breast malignancy. Due to frequent changes in the definition of these lesions, the correct diagnosis, estimation of exact prevalence, and clinical behaviour of this entity may be challenging. The aim of this study was to evaluate the prevalence, clinical features, and outcomes in a large cohort of patients with breast cancer with neuroendocrine differentiation.Patients Twenty-seven cases of breast cancer with neuroendocrine differentiation have been included in this analysis. Twenty-one cases were identified by systematic immunohistochemical re-evaluation of 465 breast cancer specimens using the neuroendocrine markers chromogranin A and synaptophysin, resulting in a prevalence of 4.5%. A further six cases were identified by a review of clinical records.Results Median age at the time of diagnosis was 61 years. 70% of patients had T2 – 4 tumors and 37% were node-positive. The most common immunohistochemical subtype was HR-positive/HER2-negative (85%). 93% were positive for synaptophysin and 48% for chromogranin A. Somatostatin receptor type 2A status was positive in 12 of 24 analyzed tumors (50%). Neuroendocrine-specific treatment with somatostatin analogues was administered in two patients. The 5-year survival rate was 70%.Conclusions Breast cancer with neuroendocrine differentiation is mostly HR-positive/HER2-negative and the diagnosis is made at a higher TNM stage than in patients with conventional invasive breast carcinoma. Moreover, breast cancer with neuroendocrine differentiation was found to be associated with impaired prognosis in several retrospective trials. Due to somatostatin receptor 2A expression, somatostatin receptor-based imaging can be used and somatostatin receptor-targeted therapy can be offered in selected cases.
Keywords: neuroendocrine neoplasia of the breast; invasive breast cancer with neuroendocrine differentiation; neuroendocrine breast cancer; neuroendocrine markers; somatostatin receptor 2A